STRATEGI KAMPANYE PARTAI NASIONALIS: PENGALAMAN PARTAI NASDEM PADA PEMILU 2019 - Sakti, Andi Muhammad Sary; Al-Hamdi, Ridho; Kurniawan, Bachtiar Dwi (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2020)
This article examines the campaign strategy of the National Democrat Party (Nasdem) in Indonesia’s 2019 legislative election. Nasdem was selected as the research object because Nasdem as a new party succeeded in political campaigns in the 2019 election and was the party that experienced the highest increase in vote from previous elections compared to the other parties. Commonly, new parties cannot succeed in reaching the parliamentary threshold. However, it is not applied for Nasdem. While most surveys predicted that Nasdem would not succeed in passing the 4 percent of the parliamentary threshold, the party proved that they were being the big five-party in the 2019 election. Theoretically, the Nasdem campaign strategy is analyzed with four mix marketing indicators so-called as 4P, namely product, price, place, and promotion, This research is a qualitative research, using the case study approach. In data-gathering, it employs a documentary study by collecting news of online mass media. The research finding demonstrates that among four mix marketing indicators to assess the Nasdem campaign strategy, price is the most influential indicator which affects the triumph of Nasdem in the 2019 legislative election, primarily the image price symbolized by the robust personality of Surya Paloh. In addition to that, the Nasdem image as the Jokowi true believer also strengthens the high popular vote of Nasdem in the 2019 legislative election.